Greenland Ice Sheet's Distinct Calving Styles Are Identified in Terminus Change Timeseries - Chris Bézu; Timothy C. Bartholomaus (Geophysical Research Letters)
Abstract At least three primary iceberg calving styles have been identified in Greenland: serac collapse, which produces falling icebergs tens of meters in length; slab capsize, which produces rotating icebergs hundreds of meters in length; and tabular rifting, which produces kilometer‐scale icebergs. However, calving styles are mostly undocumented across Greenland. Here, we develop a method to disentangle the sizes of individual calving events and map the dominant calving style at glaciers, using the characteristic properties of step retreats in satellite‐derived terminus positions. At glaciers known to frequently produce calving teleseisms, step retreats greater than 200 m account for >80% of net calved length since 2018. In contrast, at glaciers known to calve by serac failure, 200 m step retreats account <20% of net calving. Thus, terminus change timeseries can offer promising insight into the dominant calving styles at marine‐terminating glaciers.